Examining the utility of near infrared light as pre-exposure therapy to mitigate temporary noise-induced hearing loss in humans - Williams, Erin; Minesinger, Kayla; Gallagher, Hilary; Stefanson, J. R.; Bridges, Nathaniel; Jackson, Natalie; Stark, Valerie; Coto, Jennifer; Rajguru, Suhrud; Yankaskas, Kurt; Rogers, Rick; Hoffer, Michael E. (Frontiers in Neurology, 2024)
Introduction This study sought to determine the effect of Occupational Safety and Health Administration (OSHA) compliant noise on auditory health and assess whether pre-noise near infrared (NIR) light therapy can mitigate the effects of noise exposure. Methods Over four visits, participants (n = 30, NCT#: 03834714) with normal hearing completed baseline hearing health assessments followed by exposure to open ear, continuous pink noise at 94 dBA for 15 min. Immediately thereafter, post-noise hearing tests at 3000, 4000, and 6000 Hz and distortion product otoacoustic emissions (DPOAEs) were conducted along with the Modified Rhyme Test (MRT), Masking Level Difference Test (MLD), and Fixed Level Frequency Tests (FLFT) [collectively referred to as the Central and Peripheral Auditory Test Battery (CPATB)] to acquire baseline noise sensitivity profiles. Participants were then randomized to either Active or Sham NIR light therapy for 30 min binaurally to conclude Visit 1. Visit 2 (≥24 and ≤ 48 h from Visit 1) began with an additional 30-min session of Active NIR light therapy or Sham followed by repeat CPATB testing and noise exposure. Post-noise testing was again conducted immediately after noise exposure to assess the effect of NIR light therapy. The remaining visits were conducted following ≥2 weeks of noise rest in a cross-over design (i.e., those who had received Active NIR light therapy in Visits 1 and 2 received Sham therapy in Visits 3 and 4). Results Recovery hearing tests and DPOAEs were completed at the end of each visit. Participants experienced temporary threshold shifts (TTS) immediately following noise exposure, with a mean shift of 6.79 dB HL (±6.25), 10.61 dB HL (±6.89), and 7.30 dB HL (±7.25) at 3000, 4000, and 6000 Hz, respectively, though all thresholds returned to baseline at 3000, 4000, and 6000 Hz within 75 min of noise exposure. Paradoxically, Active NIR light therapy threshold shifts were statistically higher than Sham therapy at 3000 Hz (p = 0.04), but no other differences were observed at the other frequencies tested. An age sub-analysis demonstrated that TTS among younger adults were generally larger in the Sham therapy group versus Active therapy, though this was not statistically different. There were no differences in CPATB test results across Active or Sham groups. Finally, we observed no changes in auditory function or central processing following noise exposure, suggestive of healthy and resilient inner ears. Conclusion In this study, locally administered NIR prior to noise exposure did not induce a significant protective effect in mitigating noise-induced TTS. Further exploration is needed to implement effective dosage and administration for this promising otoprotective therapy.